Immune Cell Trafficking to the Liver. Issue 7 (July 2019) - Chaudhry, Sulemon; Emond, Jean; Griesemer, Adam
Abstract : The human liver is an organ with a diverse array of immunologic functions. Its unique anatomic position that leads to it receiving all the mesenteric venous blood, combined with its unique micro anatomy, allows it to serve as a sentinel for the body's immune system. Hepatocytes, biliary epithelial cells, Kupffer cells, stellate cells, and liver sinusoidal endothelial cells express key molecules that recruit and activate innate and adaptive immunity. Additionally, a diverse array of lymphoid and myeloid immune cells resides within and traffics to the liver in specific circumstances. Derangement of these trafficking mechanisms underlies the pathophysiology of autoimmune liver diseases, nonalcoholic steatohepatitis, and liver transplantation. Here, we review these pathways and interactions along with potential targets that have been identified to be exploited for therapeutic purposes.